2012
DOI: 10.1186/1477-7819-10-163
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of surgical resection and radiofrequency ablation for early hepatocellular carcinoma

Abstract: BackgroundThere is no definite agreement on the better therapy (radiofrequency ablation (RFA) versus surgical resection (SR)) for early hepatocellular carcinoma (HCC) eligible for surgical treatments. The purpose of this study is to evaluate the evidence using meta-analytical techniques.MethodsA literature search was undertaken until December 2011 to identify comparative studies evaluating survival rates, recurrence rates, and complications. Pooled odds ratios (OR) and 95% confidence intervals (95% CI) were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 36 publications
(64 reference statements)
1
39
0
1
Order By: Relevance
“…These findings are confirmed by a meta-analysis by Xu et al [140] also showing a significantly improved survival benefit for patients with early stages of HCC undergoing surgery instead of RFA. When trying to further expand indication for hepatic surgery towards HCC stage B (intermediate stage), one has to compare the outcome results from surgery and TACE.…”
Section: Surgical Approach Vs Interventional Tumor Therapysupporting
confidence: 77%
See 1 more Smart Citation
“…These findings are confirmed by a meta-analysis by Xu et al [140] also showing a significantly improved survival benefit for patients with early stages of HCC undergoing surgery instead of RFA. When trying to further expand indication for hepatic surgery towards HCC stage B (intermediate stage), one has to compare the outcome results from surgery and TACE.…”
Section: Surgical Approach Vs Interventional Tumor Therapysupporting
confidence: 77%
“…When comparing liver resection vs RFA (for patients with stage A HCC who are not suitable for transplantation), there are several meta-analyses showing that hepatic resection is superior to RFA (or PEI) for HCC with regard to recurrence-free and overall survival [38,140,151,152] . Whereas this superiority of surgery is accepted especially for tumors with diameters > 3 cm, there are some contradictory results for small HCC with a diameter < 3 cm.…”
Section: Perspectivesmentioning
confidence: 99%
“…Moreover, the formation and development of liver cancer is associated with high morbidity and mortality. 3,4 A previous study reported the application of some natural production to treat liver cancer in cultured cells, animal models and clinical investigations. This provided useful data for cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…3 Normal cells divide as many times as needed and stop. 4 They attach to other cells and stay in place in tissues. Cells become cancerous when they lose their ability to stop dividing, attach to other cells, stay where they belong, and die at the proper time.…”
Section: Introductionmentioning
confidence: 99%
“…However, many liver cancer patients fail to respond to initial chemotherapy, or they acquire drug resistance during the treatment (3). Normal cells divide as many times as needed and stop (4). They attach to other cells and stay in place in tissues.…”
Section: Introductionmentioning
confidence: 99%